Isolation of multidrug-resistant Escherichia coli O157 from goats in the Somali region of Ethiopia: A cross-sectional, abattoir-based study - Dulo, F.; Feleke, A.; Szonyi, Barbara; Fries, R.; Baumann, M.P.O.; Grace, Delia (Public Library of Science, 2015)
Toxigenic Escherichia coli (E. coli) are an important cause of gastroenteritis in developing countries. In Ethiopia, gastroenteritis due to food-borne disease is a leading cause of death. Yet, there is no surveillance for E. coli O157 and little is known about the carriage of this pathogen in Ethiopia’s livestock. This study aimed to assess the prevalence and levels of antimicrobial resistance of E. coli O157 in goat meat, feces, and environmental samples collected at a large abattoir in the Somali region of Ethiopia. The samples were enriched in modified tryptone broth containing novobiocin, and plated onto sorbitol MacConkey agar. Isolates were confirmed using indole test and latex agglutination. Antimicrobial susceptibility testing was conducted using the disk diffusion method. A total of 235 samples, including 93 goat carcass swabs, 93 cecal contents, 14 water, 20 hand, and 15 knife swabs were collected. Overall, six (2.5%) samples were contaminated with E. coli O157 of which two (2.1%) were isolated from cecal contents, three (3.2%) from carcass swabs, and one (7.1%) from water. All isolates were resistant to at least two of the 18 antimicrobials tested. Two isolates (33.3%) were resistant to more than five antimicrobials. Abattoir facilities and slaughter techniques were conducive to carcass contamination. This study highlights how poor hygiene and slaughter practice can result in contaminated meat, which is especially risky in Ethiopia because of the common practice of eating raw meat. We detect multi-resistance to drugs not used in goats, suggesting that drugs used to treat human infections may be the originators of antimicrobial resistance in livestock in this ecosystem. The isolation of multidrug-resistant E. coli O157 from goats from a remote pastoralist system highlights the need for global action on regulating and monitoring antimicrobial use in both human and animal populations.